2014
DOI: 10.4103/0378-6323.129386
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a computer based objective structured clinical examination in the assessment of undergraduate dermatology courses

Abstract: Many teaching centers have now adopted objective structured clinical examination (OSCE) as an assessment method for undergraduate dermatology courses. A modification of the standard OSCE in dermatology is computer based or electronic OSCE (eOSCE). We attempted to validate the use of a computer-based OSCE in dermatology in a group of fifth year medical students. The scores of the students in the computer-based OSCE showed a strong positive correlation with the scores on the clinical presentation (Pearson's co-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The available technology enables us to fully use online exam as a form of evaluation in future directions. Other studies have shown effectiveness in the conduct of online OSCE in comparison to traditional OSCE (Chaudhary et al, 2017;Kaliyadan et al, 2014). We have demonstrated that OSCE too can be conducted remotely without any physical contact or any compromise in achieving the learning objectives within the curriculum.…”
Section: Discussionmentioning
confidence: 71%
“…The available technology enables us to fully use online exam as a form of evaluation in future directions. Other studies have shown effectiveness in the conduct of online OSCE in comparison to traditional OSCE (Chaudhary et al, 2017;Kaliyadan et al, 2014). We have demonstrated that OSCE too can be conducted remotely without any physical contact or any compromise in achieving the learning objectives within the curriculum.…”
Section: Discussionmentioning
confidence: 71%
“…Studies that used online technologies to substitute existing skills assessments (n=4) were typically focused on digitalizing the existing assessment rubrics (Haack et al, 2017) or the assessment delivery (Snodgrass et al, 2014) in clinical or healthcare settings. Findings suggested that the digitalization of existing skills assessment was not inferior to traditional delivery (Kaliyadan et al, 2014) and enabled immediate and customized feedback (Haack et al, 2017). However, training was necessary for the implementation of digitalized skills assessment (Snodgrass et al, 2014).…”
Section: Current Research Into Online Skills Assessmentsmentioning
confidence: 99%
“…In the context of the coronavirus disease 2019 pandemic, we could even consider the use of e-OSCEs which has shown to be valid in the context of dermatology assessment. [3] Ideally, small group teaching (not just in dermatology, but for all clinical rotations) should have at least a few sessions in the classical problem-based learning format, especially for rotations in the early stages, like the fourth semester, and these too should have an assessment component covering not just knowledge/comprehension, but also soft skills such as leadership skills and communication/presentation skills. Furthermore, the large group format could use methods like team-based learning, with a component of assessment factored in.…”
mentioning
confidence: 99%